2010
DOI: 10.1130/g30342.1
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Grenvillian lithospheric mantle as a consequence of long-lived subduction beneath Laurentia

Abstract: subduction beneath Laurentia Enriched Grenvillian lithospheric mantle as a consequence of long-lived Email alerting services articles cite this article to receive free e-mail alerts when new www.gsapubs.org/cgi/alerts click Subscribe to subscribe to Geology www.gsapubs.org/subscriptions/ click Permission request to contact GSA http://www.geosociety.org/pubs/copyrt.htm#gsa click official positions of the Society. citizenship, gender, religion, or political viewpoint. Opinions presented in this publication do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…Despite this, the plutons have typical igneous wholerock chemistry and radiogenic isotope values. In order to account for the anomalous δ 18 O values, Peck et al (2004) suggested that hydrothermally altered basalts and/or oceanic sediments were subducted or underthrust be neath the Frontenac terrane during closure of an ocean basin between the Frontenac terrane and the Adirondack Highlands at or prior to 1.2 Ga. Our work supports this contention, and Chiarenzelli et al (2010) identifi ed potential fragments of the underplated basalt and enriched upper mantle shown schematically in Figure 9 of Peck et al (2004).…”
Section: Timing and Nature Of Shawinigan Magmatismsupporting
confidence: 81%
“…Despite this, the plutons have typical igneous wholerock chemistry and radiogenic isotope values. In order to account for the anomalous δ 18 O values, Peck et al (2004) suggested that hydrothermally altered basalts and/or oceanic sediments were subducted or underthrust be neath the Frontenac terrane during closure of an ocean basin between the Frontenac terrane and the Adirondack Highlands at or prior to 1.2 Ga. Our work supports this contention, and Chiarenzelli et al (2010) identifi ed potential fragments of the underplated basalt and enriched upper mantle shown schematically in Figure 9 of Peck et al (2004).…”
Section: Timing and Nature Of Shawinigan Magmatismsupporting
confidence: 81%
“…Large-ion lithophile and high field strength elements concentrations in CMGs normalized to primitive mantle (Fig. 13;Sun and McDonough, 1989) show a positive Cs anomaly and a very slight negative Nb and Ti anomaly (small, and variable calcalkaline component), but otherwise contain few distinguishable anomalies, notably lacking the pronounced subduction-related signatures seen in older arc-derived plutonic rocks of the Adirondacks (Chiarenzelli et al, 2010a;McLelland and Chiarenzelli, 1990).…”
Section: Geochemistrymentioning
confidence: 95%
“…Also shown in Figure 13 is the incompatible element trend of CMGs compared to trends of pre-Shawinigan mafic and ultramafic rocks found in the Adirondack Lowlands (Chiarenzelli et al, 2010a). Notice the relative lack of Pb, Nb, P, and Ti anomalies in CMGs.…”
Section: Geochemistrymentioning
confidence: 96%
See 2 more Smart Citations